Accuracy of the prediction of Ironman performance : relationship to training history, muscle pain and relative perception of effort during, and recovery after the race - Spijkerman, Ronel (MRC/UCT RU for Exercise and Sport Medicine, 2015)
Includes bibliographical references (leaves 52-61).